(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
In modern conditions, audit firms require high-quality software tools that expand their capabilities when applying statistical methods, collecting audit evidence, sampling, building an audit, etc. in a word, allowing to reduce the time for the audit as a whole. The article discusses the main specialized computer programs that increase the speed and quality of the audit. This article discusses the features of the use of information systems in the audit. The advantages of an automated approach to the performance of an audit assignment are primarily related to the automation of the auditor’s routine operations, which reduces labor costs, avoids mechanical errors, reduces audit time, and maintains the quality of work performed